Perencanaan Dermaga dan Dinding Penahan Tanah serta Pembuatan Website Wisata di Desa Bahu Palawa - Mega Citra Noraisyah; Andikha Prayoga; Maria Olivia Septiana; Putri Pradiastiwi; Ahmad Sila Nurwanda; Okta Pria Dinata; Yehezkiel Noverino; Rudi Waluyo (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2026)
The Building and Impact Engineering Program (TMB) at Palangka Raya University in 2025 is a form of community service based on civil engineering knowledge. The implementation of this activity took place in Bahu Palawa Village in Kahayan Tengah District, Pulang Pisau Regency, Central Kalimantan Province, with a focus on planning a wooden pier, retaining wall, as well as creating a village tourism website. The main objective of this activity is to support the development of tourism potential and village culture in a sustainable manner through improving infrastructure and digitizing tourist information. In its implementation, students carry out field surveys using simple measuring tools such as roll meters and cameras For the initial geometric measurements and verification of the existing pier conditions, interviews were conducted with village officials, and technical documents were prepared, including the Detail Engineering Design (DED) and the Cost Estimate Plan (Rencana Anggaran Biaya/RAB). In addition, a tourism website was developed to serve as the village’s official digital promotion platform, featuring the village profile, tourism potential, gallery, and an accessible location map for both the public and visitors. The final results indicate that this project successfully produced infrastructure planning and digital media that are ready for implementation, with a total estimated budget of approximately IDR IDR 4,966,843,000.00 (four billion nine hundred sixty-six million eight hundred forty-three thousand rupiah).